Clinical characteristics of self‐reported nocturia in patients with interstitial cystitis, and effects of bladder hydrodistention (with fulguration of Hunner lesions) on nocturia. Issue 2 (16th July 2018) - Otsuka, Atsushi; Suzuki, Takahisa; Aki, Ryota; Matsushita, Yuto; Tamura, Keita; Motoyama, Daisuke; Ito, Toshiki; Sugiyama, Takayuki; Miyake, Hideaki
Abstract : Objective: The aim of this study was to investigate the clinical characteristics of nocturia in patients with interstitial cystitis (IC), and the effects of bladder hydrodistention (with fulguration of Hunner lesions) on nocturia. Methods: The records of 81 patients who were diagnosed with IC were reviewed. Clinical characteristics were evaluated using the Interstitial Cystitis Symptom Index (ICSI), a visual analogue scale (VAS), and bladder diary data. Differences in characteristics between Hunner‐ and non‐Hunner‐type IC were compared. Correlations between nocturia and other clinical variables were assessed. Stepwise multiple regression analysis was performed to identify factors associated with nocturia. Further, changes in nocturia before and after hydrodistention (with fulguration of Hunner lesions) were analyzed. Results: The mean (± SD) age of patients was 62.2 ± 15.3 years. Significant differences in nocturia were observed between Hunner‐ and non‐Hunner‐type IC. Nocturia was positively correlated with age, urgency score (ICSI and VAS), mean number of urgency episodes per 24 hours and the nocturnal polyuria (NP) index, and negatively correlated with average voided volume. Age, NP index, average voided volume, and the presence of Hunner lesions were independent factors associated with nocturia. Bladder hydrodistention significantly decreased nocturia in non‐Hunner type IC without NP. In addition, regardless of the presence or absence of NP, bladder hydrodistention with fulguration of Hunner lesions significantly decreased nocturia in Hunner‐type IC. Conclusions: The severity of nocturia is associated with age, NP, average voided volume, and the presence of Hunner lesions in IC patients. Bladder hydrodistention (with fulguration of Hunner lesions) has the potential to decrease nocturia.